Lembaga Dakwah Kampus: Mahasiswa dan Aktivitas Dakwah di Universitas Maritim Raja Ali Haji - Irham , Muhammad; Pipir Romadi; Anisa Marsela; Rizal Effendi Putra; Mhd. Rafi Yahya (CV Insan Kreasi Media, 2023)
This article examines da'wah activities initiated by students in the higher education environment. Specifically, this article explores the Islamic Student Activity Unit (UKMI) Bahrul 'Ulum as a Campus Da'wah Institute (LDK) at Raja Ali Haji Maritime University in carrying out its da'wah activities. This article looks at how Islamic students initiate da'wah activities on campus by using the Campus Da'wah Institute as their vessel. The data for this article were obtained from interviews, observation and documentation as well as obtained from reading materials related to this research. This article finds that the Islamic Student Activity Unit (UKMI) Bahrul 'Ulum is the center of religious activity among Raja Ali Haji Maritime University Students. UKMI Bahru 'Ulum is used as a Campus Da'wah Institute and a coaching forum spearheaded by students with da'wah activities as its main activity. The da'wah activities initiated by LDK UKMI Bahrul 'Ulum are Cadre Training, Rihlah, Mentoring with Murabbi, Mabit, Syiar and Koran Together. All activities carried out are aimed at Syiar Islam in the campus environment and a place for fostering religious activities for students.